An improved indoor location technique using combination of kalman filter and centroid positioning - Aziz N.F.N.A.; Jamil N.; Din M.M. (Engineering and Technology Publishing, 2023)
Indoor positioning technique is used to trace the location of entities within a non-space environment riding from the incapability of GPS to do so. Most of indoor localization techniques proposed by researchers to discover an optimized solution for indoor location tracking that has high precision and accuracy. This paper proposes an improved indoor location technique by implementing Trilateration and Kalman Filter that can manipulate noise signal reduced from raw Received Signal Strength Indicator (RSSI). This paper also proposed the uses of Centroid Positioning that be amended on top of Kalman Filter which to study whether it can improve the accuracy rate or not. Upon implementing the technique, observation and comparison are made to measure the effectiveness and reliability of the uses of Kalman Filter and Centroid Positioning. Our analysis and finding show that the enhanced indoor positioning technique has improved the accuracy tremendously. 2019 Journal of Communications.